2018
DOI: 10.1111/ina.12497
|View full text |Cite
|
Sign up to set email alerts
|

The Firepower Sweep Test: A novel approach to cookstove laboratory testing

Abstract: Emissions from solid-fuel cookstoves have been linked to indoor and outdoor air pollution, climate forcing, and human disease. Although task-based laboratory protocols, such as the Water Boiling Test (WBT), overestimate the ability of improved stoves to lower emissions, WBT emissions data are commonly used to benchmark cookstove performance, estimate indoor and outdoor air pollution concentrations, estimate impacts of stove intervention projects, and select stoves for large-scale control trials. Multiple-firep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 51 publications
6
42
0
Order By: Relevance
“…While this comparison only looks at MCE as it is a commonly reported performance metric, Bilsback et al [13] showed that similar overlap between field performance and results from FST testing can be seen for PM 2.5 and CO emission factors. Medina et al [15] also showed that testing cookstoves by replicating local cooking cycles in rural Mexico produced MCEs and PM 2.5 and CO emission factors that better represented those for the local stoves during field performance.…”
Section: Combustion Efficiency and Comparison With Laboratory Datamentioning
confidence: 98%
See 3 more Smart Citations
“…While this comparison only looks at MCE as it is a commonly reported performance metric, Bilsback et al [13] showed that similar overlap between field performance and results from FST testing can be seen for PM 2.5 and CO emission factors. Medina et al [15] also showed that testing cookstoves by replicating local cooking cycles in rural Mexico produced MCEs and PM 2.5 and CO emission factors that better represented those for the local stoves during field performance.…”
Section: Combustion Efficiency and Comparison With Laboratory Datamentioning
confidence: 98%
“…MCEs from Bilsback et al [13] using the FST have been included to demonstrate how new protocols have been developed to potentially bridge the gap between laboratory and field performance. Compared to the WBT, which is limited to high-power and simmering phases, the FST includes low, medium, and high firepower phases, as well as start-up and shutdown phases, which are all measured individually.…”
Section: Combustion Efficiency and Comparison With Laboratory Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This work was part of United States Environmental Protection Agency (US EPA) STAR project that included complimentary laboratory, field, and modeling studies looking at the global health and climate impacts of household energy use. [23][24][25][26] Stove-use monitoring in the field was conducted in China, Honduras, Uganda, and India in conjunction with emission testing campaigns. The stove-fuel combinations were selected, in consultation with field partners, to represent typical solid-fuel cooking and heating technologies in each respective region.…”
Section: Study Overviewmentioning
confidence: 99%